THE RELATIONSHIP OF MENARCHE AGE WITH BREAST CANCER EVENTS IN WOMEN AGE 25-50 YEARS IN THE SHORT CENTER OF INDONESIA BREAST CANCER FOUNDATION (YKPI) JAKARTA: HUBUNGAN USIA MENARCHE DENGAN KEJADIAN KANKER PAYUDARA PADA WANITA USIA 25-50 TAHUN DI RUMAH SINGGAH YAYASAN KANKER PAYUDARA INDONESIA (YKPI) JAKARTA - Magdalena Agu Yosali; Nurlita Bintari (Wijaya Husada, 2019)
Breast cancer is a cancer that occurs most often among women, which affects the 1,5 million women every year and cause the death toll due to cancer is found among women.In 2015, 570.000 women dying of breast cancer, which is about 15 % of cancer death among women.The incident breast cancer relating to the risk of breast cancer, the main risk factors associated with the incident breast cancer is the state of hormonal and genetic. Family history hormonal factors can be influenced by some one is the age of menarche To know relations age menarche with the occurrence of breast cancer in women age 25-55 years in women in Yayasan Kanker Payudara Indonesia ( YKPI ) in 2019. This is the kind of research quantitative research with a design research analytic used the cross sectional performed at Yayasan Kanker Payudara Indonesia (YKPI) Jakarta in 2019 , respondents were 30 .Uses the technique total sampling .An instrument used is the questionnaire and a observation and analysis techniques using spearman.The results of the analysis of 30 the smallest number of respondents there are 22 ( 100 % ) a woman whose period menarche at the age of ≤ 12 years the proportion who experienced breast cancer , from 30 the smallest number of respondents there are 20 ( 100 % ) a woman whose period menarche ≤ 12 year have been of breast cancer 8 ( 80 % ) a woman whose period menarche > 12 year have been of breast cancer , 2 ( 20% ) a woman whose period menarche & gt; 12 years they had experienced no cancer of the breast , sehigga ho refused to play host to which would mean there are even closer ties between the between the ages of menarche with an instance of cancer of the breast . P value = 0,007 .The value of persons of very = 0,800 As for advice for the research can be used as evalusi in providing information about breast cancer.